Aberrant Salience and Motivation as Factors in the Formation of Belief in Scientifically Unaccepted Phenomena - Irwin, Harvey Jon (Journal of Scientific Exploration, 2014)
<!--[if gte mso 9]> <![endif]--><span style="font-size: 11.0pt; line-height: 115%; font-family: "Times New Roman","serif"; mso-fareast-font-family: Calibri; mso-ansi-language: EN-GB; mso-fareast-language: EN-US; mso-bidi-language: AR-SA;" lang="EN-GB">The aim of this study was to investigate relationships between the endorsement of beliefs in scientifically unaccepted phenomena and two psychological domains, namely proneness to aberrant salience and fundamental dimensions of human motivation. The project was undertaken as an online survey of 104 university students. “New Age” or paranormal beliefs were found to be related both to a proneness to aberrant salience and to a need for intimacy, but no such relationships were evident for traditional religious beliefs. The findings are discussed in terms of the psychological mechanisms that may underlie the development of beliefs in paranormal phenomena. Keywords: scientifically unaccepted beliefs―aberrant salience―need for control―need for intimacy <!--[if gte mso 9]> Normal 0 false false false EN-AU X-NONE X-NONE <![endif]--><!--[if gte mso 9]> <![endif]--><!--[if gte mso 10]> <mce:style><! /* Style Definitions */ table.MsoNormalTable {mso-style-name:"Table Normal"; mso-tstyle-rowband-size:0; mso-tstyle-colband-size:0; mso-style-noshow:yes; mso-style-priority:99; mso-style-parent:""; mso-padding-alt:0cm 5.4pt 0cm 5.4pt; mso-para-margin:0cm; mso-para-margin-bottom:.0001pt; mso-pagination:widow-orphan; font-size:10.0pt; font-family:"Calibri","sans-serif";} --> <!--[endif] -->